“Mon semblable, mon frère”: Brothers Petrarch and Literary Self-Construction - Majumder, Doyeeta (Renaissance and Reformation / Renaissance et Réforme, 2022)
This article posits that in the texts (both epistolary and otherwise) associated explicitly with his brother Gherardo, Petrarch does not just showcase the familiar, intimate style that characterizes the whole corpus of his familiar letters but also presents some of the most acutely reflexive ruminations on his own stylistic and, by extension, literary practices. In the Gherardine letters, as well as in the first eclogue of the Bucolicum carmen, which is attached to one of these letters, Petrarch rehearses the highlights of the debates surrounding rhetorical style that were being played out in Trecento Europe, while simultaneously demonstrating his attempts to engage with alternatives to the modes of Ciceronian writing, both grand and intimate. In these works, Petrarch’s brother comes to embody this stylistic alternative.